Evaluating the effects of Moringa oleifera on atherogenic lipoprotein indices of HIV infected Nigerian adults on tenofovir-based antiretroviral regimen - Anyanwu, Chinwe F.; Obianime, Wolie A.; Siminialayi, Iyeopu M.; Aigbogun, Eric O. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The administration of tenofovir (TDF) based (tenofovir/ lamivudine/efavirenz) antiretroviral regimen for the management of HIV has remained a concern to both clinicians and patients, thus necessitating the need for suitable supplement for the management of ART induced metabolic abnormalities. The study evaluated the effects of Moringa supplementation on the atherogenic lipoprotein indices of HIV patients on TDF-based regimen at the University of Port Harcourt Teaching Hospital, Rivers State, Nigeria. Methods: The study was designed as a time dependent investigation structured into 3 visits, visit 1 (cross sectional, baseline), visit 2 (4 weeks after administration) and visit 3 (12 weeks post administration). Subjects recruited (140) into this study comprised of two groups, TDF-M (n=56, administered Moringa Supplement) and TDF-NM (n=84, no supplement). Results: At baseline, more than 50% of the patients had at least one abnormal atherogenic lipoprotein indices (Log (TC/HDL-C) = 85.7%, TC/HDL-C=58.5% and LDL-C/HDL-C=51.4%), although at lower limits. At the end of 12 weeks of Moringa supplement administration, the results showed subjects in the TDF-M group who were at risk of CVD had fallen to 20%, indicating a dramatic (40.4%) decrease, while the prevalence of TDF-NM subject at risk of CVD rose to 53.6% (χ2=26.67, P <0.001). HIV patients on TDF-based regime, who were at risk of CVD had elevated triglycerides and low-density lipoprotein cholesterols which inversely affected the levels of high-density lipoprotein and negatively impacting the atherogenic indices. Conclusions: Moringa oleifera supplementation may be helpful in ameliorating the metabolic abnormalities associated with HIV patients on TDF-based regimen.